Foreign investment and the Brazilian real estate market - Lima Jr., João da Rocha; Alencar, Claudio Tavares de (International Journal of Strategic Property Management, 2010)
This article discusses the main aspects of the Brazilian real estate market in order to illustrate if it would be attractive for a typical American real estate investor to buy office‐building portfolios in Brazil. The article emphasizes: [i] — the regulatory frontiers, comparing investment securitization, using a typical American REIT structure, with the Brazilian solution, using the Fundo de Investimento Imobiliário — FII; [ii] — the investment quality attributes in the Brazilian market, using an office building prototype, and [iii] ‐ the comparison of [risk vs. yield] generated by an investment in the Brazilian market, using a FII, benchmarked against an existing REIT (OFFICE SUB‐SECTOR) in the USA market. We conclude that investing dollars exchanged for Reais [the Brazilian currency] in a FII with a triple A office‐building portfolio in the São Paulo marketplace will yield an annual income and a premium return above an American REIT investment. The highly aggressive scenario, along with the strong persistent exchange rate detachment to the IGP‐M variations, plus instabilities affecting the generation of income, and even if we adopt a 300‐point margin for the Brazil‐Risk level, demonstrates that an investment opportunity in the Brazilian market, in the segment we have analyzed, outperforms an equivalent investment in the American market. First published online: 18 Oct 2010